Adoptive transfer of effector CD8(+) T cells derived from central memory cells establishes persistent T cell memory in primates - Berger, Carolina (American Society for Clinical Investigation, 2007)

(untitled)
The adoptive transfer of antigen-specific T cells that have been expanded ex vivo is being actively pursued to treat infections and malignancy in humans. The T cell populations that are available for adoptive immunotherapy include both effector memory and central memory cells, and these differ in phenotype, function, and homing. The efficacy of adoptive immunotherapy requires that transferred T cells persist in vivo, but identifying T cells that can reproducibly survive in vivo after they have been numerically expanded by in vitro culture has proven difficult. Here we show that in macaques, antigen-specific CD8(+) T cell clones derived from central memory T cells, but not effector memory T cells, persisted long-term in vivo, reacquired phenotypic and functional properties of memory T cells, and occupied memory T cell niches. These results demonstrate that clonally derived CD8(+) T cells isolated from central memory T cells are distinct from those derived from effector memory T cells and retain an intrinsic capacity that enables them to survive after adoptive transfer and revert to the memory cell pool. These results could have significant implications for the selection of T cells to expand or to engineer for adoptive immunotherapy of human infections or malignancy.